The inferomedial femoral neck is compromised by age but not disease: Fracture toughness and the multifactorial mechanisms comprising reference point microindentation. (November 2017) - Jenkins, T.; Katsamenis, O.L.; Andriotis, O.G.; Coutts, L.V.; Carter, B.; Dunlop, D.G.; Oreffo, R.O.C.; Cooper, C.; Harvey, N.C.; Thurner, P.J.; the OStEO group,
Abstract: The influence of ageing on the fracture mechanics of cortical bone tissue is well documented, though little is known about if and how related material properties are further affected in two of the most prominent musculoskeletal diseases, osteoporosis and osteoarthritis (OA). The femoral neck, in close proximity to the most pertinent osteoporotic fracture site and near the hip joint affected by osteoarthritis, is a site of particular interest for investigation. We have recently shown that Reference Point micro-Indentation (RPI) detects differences between cortical bone from the femoral neck of healthy, osteoporotic fractured and osteoarthritic hip replacement patients. RPI is a new technique with potential for in vivo bone quality assessment. However, interpretation of RPI results is limited because the specific changes in bone properties with pathology are not well understood and, further, because it is not conclusive what properties are being assessed by RPI. Here, we investigate whether the differences previously detected between healthy and diseased cortical bone from the femoral neck might reflect changes in fracture toughness. Together with this, we investigate which additional properties are reflected in RPI measures. RPI (using the Biodent device) and fracture toughness tests were conducted on samples from the inferomedial neck of bone resected from donors with: OA (41 samples from 15 donors), osteoporosis (48 samples from 14 donors) and non age-matched cadaveric controls (37 samples from 10 donoros) with no history of bone disease. Further, a subset of indented samples were imaged using micro-computed tomography (3 osteoporotic and 4 control samples each from different donors) as well as fluorescence microscopy in combination with serial sectioning after basic fuchsin staining (7 osteoporotic and 5 control samples from 5 osteoporotic and 5 control donors). In this study, the bulk indentation and fracture resistance properties of the inferomedial femoral neck in osteoporotic fracture, severe OA and control bone were comparable (p > 0.05 for fracture properties and <10% difference for indentation) but fracture toughness reduced with advancing age (7.0% per decade, r = −0.36, p = 0.029). Further, RPI properties (in particular, the indentation distance increase, IDI) showed partial correlation with fracture toughness (r = −0.40, p = 0.023) or derived elastic modulus (r = −0.40, p = 0.023). Multimodal indent imaging revealed evidence of toughening mechanisms (i.e. crack deflection, bridging and microcracking), elastoplastic response (in terms of the non-conical imprint shape and presence of pile-up) and correlation of RPI with damage extent (up to r = 0.79, p = 0.034) and indent size (up to r = 0.82, p < 0.001). Therefore, crack resistance, deformation resistance and, additionally, micro-structure (porosity: r = 0.93, p = 0.002 as well as pore proximity: r = −0.55, p = 0.027 for correlation with IDI) are all contributory to RPI. Consequently, it becomes clear that RPI measures represent a multitude of properties, various aspects of bone quality, but are not necessarily strongly correlated to a single mechanical property. In addition, osteoporosis or osteoarthritis do not seem to further influence fracture toughness of the inferomedial femoral neck beyond natural ageing. Since bone is highly heterogeneous, whether this finding can be extended to the whole femoral neck or whether it also holds true for other femoral neck quadrants or other material properties remains to be shown. Graphical abstract: fx1 Highlights: Osteoporosis and OA have minimal influence on femoral neck fracture toughness. Reference point indentation (RPI) has some independence from fracture toughness. Porosity, microdamage and elastoplastic properties contribute to RPI.